An analytical review for multipath routing in Mobile Ad Hoc Networks. (27th January 2010) - Zahary, Ammar; Ayesh, Aladdin
Multipath routing is a new extension to many traditional routing protocols in MANETs. Using multipath routing in MANETs can save energy, reduce frequent routing update, enhance data transmission rates, and increase wireless network bandwidth. This paper introduces an analytical review for multipath routing in MANETs covering its applications, classification, and design issues. A simulation-based analytical evaluation is presented in this review using NS2 for AODV and its multipath extensions namely, AOMDV and MRAODV against two traditional multipath routing protocols namely, DSR and TORA. Simulation results show that traditional multipath protocols outperform the single path version of AODV in terms of packet delivery fraction, routing packets overhead, and throughput while AODV has better performance in terms of average end-to-end delay. AODV extensions outperforms traditional protocols in terms of packet delivery fraction and average end-to-end delay.